1980
DOI: 10.1038/clpt.1980.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gastric pH on digoxin biotransformation

Abstract: 3H-digoxin-12 alpha and unlabeled digoxin were administered down a nasogastric tube and digoxin, digoxyigenin and its mono- and bis-digitoxosides, and pH were assayed in gastric fluid of 6 healthy subjects at intervals for 90 min each under 4 conditions: pentagastrin infusion 6 micrograms/kg/hr with the subjects ambulatory and supine, and saline infusion ambulatory and supine. Intragastric hydrolysis occurred at roughly the same rate as reported in vitro. At 90 min, an average of 12.5% of the radioactivity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…The recovery of hydrolytic metabolites mainly after oral intake of digoxin is consistent with previous reports demonstrating intragastric hydrolysis of the glycoside (Beermann et al, 1972.;Gault et al, 1980). Also consistent with a previous study (Magnusson et al, 1982b) non-extractable metabolites, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The recovery of hydrolytic metabolites mainly after oral intake of digoxin is consistent with previous reports demonstrating intragastric hydrolysis of the glycoside (Beermann et al, 1972.;Gault et al, 1980). Also consistent with a previous study (Magnusson et al, 1982b) non-extractable metabolites, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…Several factors have been discussed that may affect the extent of digoxin absorption, such as changes in intragastric pH 27 and bacterial flora. 25 To avoid these gastrointestinal effects, we administered digoxin intravenously in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Solubility, dissolution rate, particle size, partition coefficient, pH, pK a , stability, gastrointestinal motility patterns, volume and flow rate of gastrointestinal contents, as well as membrane permeability have been found to influence drug absorption from the gastrointestinal tract. [1][2][3][4][5][6] It can be shown that the flux or the amount of drug transported per unit time and per unit area of the membrane is a function of the permeability of the drug and the concentration gradient across the gut and the systemic circulation. Maximum drug absorption occurs when the drug has maximum permeability and maximum concentration (saturation solubility) at the site of absorption.…”
Section: Introductionmentioning
confidence: 99%